Impact of Retail Service Quality on Customer Reactions : The Mediating Effect of Retailer Personality - Rashid, Abdul; Rokade, Varsha (Indian Journal of Marketing, 2023)
Purpose : The objective of this research was to assess the impact of retail service quality on customer reactions, with retailer personality as a mediator for Indian organized food and grocery customers based in four metro cities (New Delhi, Mumbai, Kolkata, and Chennai) of India. Methodology : A survey was conducted with 410 customers who stepped out from the organized retail stores after shopping for groceries. A conceptual model has been proposed based on the linkages established through the literature review. Statistical Packages for Social Sciences (23v) and Smart Partial Least Square (3.2.7v) were applied to run exploratory and confirmatory factor analysis, respectively. The hypotheses were validated through PLS structural equation modeling. Findings : The outcomes revealed that retailer personality partially mediated the relationship between retail service quality and customer reactions. Research Limitations/Implications : Due to the limited availability of resources, the generalizability of the results cannot be done. The results can be different in various cultural settings. Practical Implications : Improved retail service quality can be a consequence of exhibited humble and sophisticated retailer personality, resulting in enhanced customer reactions (customer satisfaction, trust, and loyalty). Introversion and disingenuousness attributes of a retailer deteriorate the retailer’s personality and consequently cause harm to customer reactions. Thus, along with rendering good service quality, retailers should show a humble and sophisticated personality to gain improved customer reactions. Originality/Value : The present study strove to draw a consolidated approach of the effect of traits of retailer personality on customer reactions with special reference to the Indian context.